(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the safety of pedicle screw fixation of the spine by free hand technique in terms of screw malposition and screw related post-operative complications. Methods: This descriptive study was conducted in Orthopedic department Lady Reading Hospital Peshawar Pakistan from 23rd April 2017 to 23rd March 2020.Patients of either gender and age operated with pedicle screw fixation of the spine by free hand technique using universal entry point were included. Post-operative radiographs of the spine were utilized for screw position. Patients with malposition radiographic screws and those with screw related post-operative complications were screened with CT scan of the spine. CT based position of the pedicle screw was classified as per Zhang classification as type 0 (good), type 1 (Acceptable), type 2 (Unacceptable) and type 3 (Grievous). Revision surgery was performed for symptomatic pedicle screws and type 2 and type 3 malposition screws. Results: The total number of patients enrolled in our study were 96. Mean age was 34.20±9 years (range 10 to 70 years). Male patients were 45(46.9%) and female 51(53.1%). Total number of screws were 717 with maximum number of screws (n=425, 59.27%) in lumbar spine followed by thoracic spine (n=250, 34.87%) and sacral spine (n=42, 5.86%). Radiologically 684(95.40%) screws were within the pedicles and patients were without any symptoms while 33(4.6%) screws were malposition. CT scan classified 29(4.0%) malposition screws as type 1 but the patients were asymptomatic. Only 3(0.4%) screws in two patients were symptomatic type 2 and revision was done. No screw related vascular or visceral complication was reported. Conclusion: Free hand technique of pedicle screw fixation using universal entry point is a safe and reliable method in the absence of advance navigation system. Thorough knowledge of the spine, anatomy of the vertebrae and surgeon’s experience are however mandatory for safe placement of pedicle screw with free hand technique.